1987
DOI: 10.1002/ppul.1950030506
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary mechanics in normal infants and young children during first 5 years of life

Abstract: To characterize lung function in young children we measured lung compliance and pulmonary conductance in 40 normal infants and children ranging in age from the newborn period to 5 years. Inspiratory and expiratory flow was measured by a pneumotachograph, esophageal pressure through a water-filled feeding tube, and functional residual capacity (FRC) by a N2 washout technique. The esophageal pressure change per breath [(mean +/- SD) 7.3 +/- 1.4 cm H2O] and specific compliance (75 +/- 13 ml/cm H2O/L-FRC) did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 24 publications
2
21
2
Order By: Relevance
“…We corrected these measurements to the patients' weight to standardize the measurements for size. However, previous investigators have demonstrated that airway conductance does not have a linear relationship to size in healthy newborns, with the airways relatively more developed in small infants (44). Therefore, the greater PEF that we observed in the TO group may be secondary to prematurity rather than an effect of TO itself.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…We corrected these measurements to the patients' weight to standardize the measurements for size. However, previous investigators have demonstrated that airway conductance does not have a linear relationship to size in healthy newborns, with the airways relatively more developed in small infants (44). Therefore, the greater PEF that we observed in the TO group may be secondary to prematurity rather than an effect of TO itself.…”
Section: Discussioncontrasting
confidence: 51%
“…We did not perform lung volume measurements by gas dilution or lung morphologic examinations. However, the modest increases in Crs in this study could be secondary to increased fetal lung growth in the TO group (44). Although V E had a wide range, the values were in the normal range (47) and were highly associated with PaCO 2 (higher V E associated with lower PaCO 2 ), which was tightly controlled throughout the perioperative period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…SIVAN and co-workers [4] have published data on six children with normal lungs at the (usual) 2-4 cmH 2 O PEEP chosen by clinicians in these circumstances. Two children were close to the predicted values of GERHARDT et al [61] (18-22 mL·kg -1 ; mean= 20.4 mL·kg -1 ) and the other four were 39-52% higher. They came back into the ''normal" range only when PEEP was removed.…”
Section: Normal Values: Mechanically Assisted Breathingsupporting
confidence: 50%
“…The decision to normalize each patient's VT and dynamic compliance to their body weight was based on two factors: First, before any weight correction, the range of values obtained was much wider for both the modified RSB and modified CROP indices. As a result, it was difficult to identify a cutoff value that clearly differentiated between the successful and unsuccessful weaning groups (data not shown); Second, it is common practice to report the VT in cc/kg and clinical investigation 7 has shown that changes in dynamic compliance are highly correlated with the patient's body weight. It follows, therefore, that the VT and the dynamic compliance should be normalized for the patient's weight in kilograms.…”
Section: Adaptation Of Indexes To Pediatric Patientsmentioning
confidence: 93%